Proses Adopsi Inovasi Rumah Burung Hantu (RUBUHA) di Desa Wonosari Kecamatan Puger Kabupaten Jember - Pambudi, Andika; Puspaningrum, Diah; Novikarumsari, Nurul Dwi; Rokhani, Rokhani (Suluh Pembangunan : Journal of Extension and Development, 2025)
The Owl House is an innovation to help farmers protect their crops from pests, especially rats. Rat pests are a problem for farmers in Wonosari Village because they cause damage to their crops. The damage to the crops leads to a reduction in the farmer’s yield, which can affect their income. The research site was purposively selected in Wonosari Village, Puger Subdistrict, Jember Regency. The method used in this research is qualitative. Informants were identified through snowball sampling technique. Data collection methods used include interview with informants, field observation, and documentation. The results show that the process of adopting of innovations by farmers includes: (1) innovation information sources are agricultural extension workers and East West Company, Farmers' knowledge includes how to work, functions and benefits of innovation., (2) farmers accept innovations after knowing the characteristics of the Owl House innovation, (3) farmers decide to apply innovations obtained from assistance and self-help, (4) procurement of Owl Houses comes from assistance and self-help with problems that arise are illegal shooting of owls and lack of farmer cohesiveness, (5) farmers are willing to apply innovations on an ongoing basis as a form of anticipation and hope to benefit from the application of Owl Houses.